Learned Discussions of Indulgences for the Dead in the Middle Ages - Shaffern, Robert W. (Church history, 1992)
By the thirteenth century, Latin Christians had been dispensing and collecting indulgences for two centuries. Though indulgentia was a relatively late term, and first the favorite of thirteenth-century Dominican theologians, remissions of temporal penalty for sin had been granted since the eleventh century, whether they were known as remissiones or relaxationes, the two most popular terms of eleventh- and twelfth-century ecclesiastics. Bishops granted partial indulgences for visitations of holy places. Partial indulgences remitted a fraction of all penalty incurred through sin. Contributions to pious works, such as church, hospital, or bridge constructions, were also rewarded with indulgences. Other prelates granted indulgences until Lateran IV. The popes granted both partial and plenary indulgences (those which remitted all penalty for having sinned). They granted partial indulgences for much the same reasons as other bishops. Plenary indulgences were almost exclusively granted to crusaders or contributors to crusades.